Pelatihan Literasi Keuangan Dalam Meningkatkan Kesejahteraan Keluarga Bagi Ibu Rumah Tangga di Desa Bajur Kabupaten Lombok Barat - Baiq Herdina Septika; Tama Krisnahadi; Menik Aryani; Yayang Erry Wulandari; Ratna Azizah Mashami (Jurnal Pengabdian UNDIKMA, 2020)
The purpose of this service activity is to conduct education on planning and managing household finances more effectively and optimally so that it can improve family welfare for housewives in Bajur village. The methods of implementing this activity are lectures, discussions and exercises. The lecture consists of delivering material related to the definition of a personal or family financial management system and the importance of such management for the good and the future of the family. Participants are also trained to make the correct income and expenditure budget manually. Participants in this service activity were a group of PKK women in Bajur Village, totaling around 35 people. The result of service activities is that more than 80% of participants attended, this was calculated from the number of participants of around 33 people who participated in this activity. Most of the participants (85%) understand the household income and expenditure budget, are able to set a priority scale for needs and are able to prepare household income and expenditure budgets correctly. This activity ran smoothly and received a very positive response from the participants. This can be seen from the participants who enthusiastically participated in the event from start to finish and actively discussed issues surrounding family financial management.